First report of sunflower chlorotic mottle virus infecting sunflower plants in Brazil - Vinicius Henrique Bello; Gabriel Madoglio Favara; Gustavo Verruma Bernardi; Jorge Alberto Marques Rezende; Renato Barbosa Salaroli; Elliot Watanabe Kitajima (Scientia Agricola, 2022)
ABSTRACT Sunflower (Helianthus annuus) plants showing symptoms of chlorosis, mosaic, chlorotic ringspot, and necrosis on younger leaves were found in a small experimental plot in Piracicaba, in the state of São Paulo, Brazil. Preliminary examinations by transmission electron microscopy of symptomatic leaf tissue revealed flexuous filamentous particles 13-15 nm wide and 700-750 nm long, and cytoplasmatic cylindrical inclusions typical of those found in plant cells infected by members of the Potyvirus genus. Total RNA extracted from symptomatic leaves and subjected to RT-PCR followed by partial nucleotide sequencing confirmed the presence of a potyvirus in the affected plants, which was identified as sunflower chlorotic mottle virus (SuCMoV), a member of the Sunflower chlorotic mottle virus (genus Potyvirus, family Potyviridae) species. Mechanical transmission assays with extracts of symptomatic sunflower leaves reproduced the original symptoms in sunflowers, mosaic symptoms in Zinnia elegans, and chlorotic local lesions in Chenopodium amaranticolor and C. quinoa. Sunflower and zinnia plants became infected after aphid transmission experiments with Myzus persicae. RT-PCR tests using specific primers for SuCMoV confirmed the presence of this virus in experimentally infected plants, meeting the criteria of Koch’s postulate. This is the first report of SuCMoV infecting sunflower plants in Brazil.